Why language matters for theory of mind - Astington, Janet W.; Baird, Jodie A. (Jodie Alison), 1973- (OUP E-Books., 2005)
An exploration of how children develop an understanding of the theory of mind: the concept that people are mental beings, who have beliefs, desires, emotions, & intentions, & whose actions & interactions can be interpreted & explained by taking account of these mental states.